Towards a Learner-centred Approach: Interactive Online Peer Assessment - Naicker, Visvanathan; Bayat, Abdullah (South African Journal of Higher Education, 2016)
The tremendous workload produced by multiple assessments that aim for a learner-centered approach to learning in huge classes and the inability to provide results timeously, often results in lecturers’ maintaining teacher-centered approaches to learning even if they appreciate the benefits of learner-centered approaches. Online-peer-assessment can lessen the workload on lecturers and may be an important step towards designing courses that are learner-centered. In this study we report on the lessons and experiences of an interactive online peer assessment system. An evaluative case-study approach was undertaken. The theoretical underpinning underlying this study is activity theory. Therefore, lecturers need to monitor and evaluate the progress of the students who have undertaken this course. Interactive online-peer assessment can be enhanced if support structures and tools are readily available. For interactive online peer assessment to work there needs to be a paradigm shift at an institutional level, at the lecturer level, as well as role clarity, and a willingness on the part of the students to accept a shift in understanding their role in learning. Some of the findings indicated that technical problems experienced during the course by students also contributed to their negative attitudes toward interactive online-peer assessment.